2022
DOI: 10.3390/antibiotics11070843
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Antibiotic Resistance Patterns Affect Visual Outcome Treating Acute Endophthalmitis

Abstract: Background: Examining the effect of antibiotic resistance, use of intravitreal antibiotics and systemic corticosteroids on visual outcome of eyes with acute endophthalmitis. Methods: We included 226 eyes with acute endophthalmitis, treated using a standardized protocol. Visual outcome up to 12 months was assessed related to biopsy results, antibiotics resistance and treatment regimens. Results: Vitreous biopsies were more likely to be culture-positive (41.1%) than anterior chamber biopsies (21.6%, p < 0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Visual outcome based upon the proportion of patients without severe vision loss is better than previously reported, which could be attributable to differences in study population, research protocols and treatment regimens. Wu et al, conducted a study utilising a similar protocol and found a higher rate of severe vision loss compared to our cohort (42.9% vs. 67.7%) and a worse mean final BCVA (2.19 LogMar vs. 1.18 LogMar) [ 5 ]. As presenting vision and culture positivity rates were equivocal, other possible explanations for this difference could be the higher degree of reported antimicrobial resistance and lower rates of early vitrectomy (50.4% vs. 4.0%).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Visual outcome based upon the proportion of patients without severe vision loss is better than previously reported, which could be attributable to differences in study population, research protocols and treatment regimens. Wu et al, conducted a study utilising a similar protocol and found a higher rate of severe vision loss compared to our cohort (42.9% vs. 67.7%) and a worse mean final BCVA (2.19 LogMar vs. 1.18 LogMar) [ 5 ]. As presenting vision and culture positivity rates were equivocal, other possible explanations for this difference could be the higher degree of reported antimicrobial resistance and lower rates of early vitrectomy (50.4% vs. 4.0%).…”
Section: Discussionmentioning
confidence: 80%
“…Our cohort of culture-positive endophthalmitis (n = 207) is the largest to date that addresses conflicting views about the impact of antimicrobial resistance on visual outcomes. Whilst Wu et al, (n = 99) found that antimicrobial resistance was not associated with a risk of vision loss, Choi et al, (n = 82) found that resistance to Vancomycin or third-generation cephalosporins was associated with a 75% lower chance of achieving VA better than counting fingers [ 5 , 41 ]. Further complicating matters is the lack of concordance between in vitro antimicrobial sensitivities and clinical response, which is reflective of greater concentrations of antimicrobials following intravitreal administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean resistance rates were between 57 and 61% for various fluoroquinolones, though there was no mention of the route of administration [60]. An additional study found 16.7% of culture-positive endophthalmitis cases were resistant to moxifloxacin [61 ▪ ].…”
Section: Resistance To Intracameral Moxifloxacinmentioning
confidence: 99%